Developing Continuing Education for Ohio’s Local Boards of Health - Diana M. Kingsbury; Matthew Stefanak; Ken Slenkovich (Ohio Journal of Public Health, 2020)
Background: Public health functions at the county level and city level through the work of local health departments (LHDs). Local boards of health (LBoHs) work closely with LHDs as an administrative oversight body. In 2013, legislation was passed in the state of Ohio pertaining to the accreditation of LHDs, which included a provision requiring that Ohio’s LBoH members engage in 2 hours of continuing education (CE) per year. To assist LBoHs in fulfilling these requirements, a partnership was developed between the Ohio Association of Boards of Health (OABH) and the Kent State University College of Public Health (KSU-CPH) to deliver CE content. Methods: The process for developing the CE modules encompasses 3 steps: (1) needs assessment, (2) module development and delivery, and (3) evaluation. Feedback was solicited from Ohio’s LBoH members to determine topics of interest for CE modules. Taking this feedback, a curated set of 8 modules will be developed. Module content will be derived from graduate courses within KSU-CPH as well as from subject matter experts. The modules will be delivered online to LBoH members during their regularly scheduled meetings. Results: This program proposes to fulfill state requirements that LBoH members regularly engage in CE. Partner-ing with KSU-CPH allows for the use of academic content in these trainings. Conclusion: An adequately trained public health workforce is essential for a well-functioning public health system, which includes governing entities like LBoHs. There is limited understanding of how workforce development can be targeted specifically to LBoHs. This CE program contributes to current efforts to promote workforce development within the field of public health.
Keywords: Workforce development; Continuing education; Boards of health; Local public health; Public health governance